Kajian Terapan Interior Signage di Gedung Q Universitas Kristen Petra - Liong Jessica Angela; Diana Thamrin; Celline Junica Pradjonggo (Intra, 2019)
Interior signage a small thing but is very influential to human activities, because without information about directions, often people can get lost and waste time just for wayfinding. Building Q is a new building in Petra Christian University which has been operating since 2017. There are already several interior signages in building Q, but they are still in complete and some have not been up to standards of good interior signage. Therefore, this study was conducted to determine the effevtiveness of interior signage in the Petra Christian University Q building and provide effective interior signage design solution for Petra Christian University. Data was obtained through observation, documentation, distributing questionnaires to building users and literature review. Data was analysis through descriptive qualitative method with 5 stages (exploration, define, ideate, visualitation, and evaluation) by paying attention to signage parameters. The proposed design solutions include: using university branding as the color to be used, using the shape of the Q building as the basis for the shape of the building’s Q interior, and changing the font to make it easier to read